“Mãe é quem deseja”: uma contribuição psicanalítica sobre o exercício da maternidade no contexto da adoção - Almeida, Susana Gomes (Universidade Federal do Tocantins, 2023)
This study aimed to understand the experience of motherhood in the context of adoption, based on the theoretical framework of psychoanalysis, especially regarding the desire of filiation. For this purpose, this study was based on qualitative, exploratory, and field research, in which a semi-structured interview was conducted with an over 21 years old adult female participant who exercises motherhood through adoption. The data were analyzed using Bardin’s content analysis and the categories were discussed using the theoretical framework of Freud and Lacan's psychoanalysis, with the support of commentators. Reflecting on motherhood from the perspective of the desire of filiation means recognizing the various forms that present themselves as possibilities to transform this project of filiation into the experience of motherhood. In this sense, recognizing adoption as a valid form of exercising motherhood implies considering another perspective on motherhood experienced by women. It is necessary to recognize the multiple facets that involves the desire for motherhood, especially when they are not related to the gestation of a child. Based on this principle, it is necessary to question what leads women and men to think about having children and, subsequently, what sustains mothers and fathers in the process of transitioning to the parental position or parenthood. Thus, reflecting on adoption’s motherhood from the perspective of the desire of filiation implies validating the bond between mother and child when they are not connected by blood, considering the naming and sustenance of this role by a woman, as well as the diversity of contemporary family arrangements. Furthermore, in terms of psychoanalytic clinical practice, it is necessary to investigate the plasticity of the desire for motherhood and the experienced meaning in this perspective, seeking to understand the process of filiation and the adoption of a child in a woman's imagination, as well as the resources used to sustain the maternal function.